Uso de tecnologías digitales en la educación matemática en Costa Rica (ING) - De Faria, Edison (2003)
This article gives a brief summary of research policies and the use of technology in Costa Rica, describing how Costa Rican High School mathematics teachers use computers and calculators in the mathematical teaching and learning process. The data analyzed were gathered in a questionnaire taken by High School mathematics teachers in 2000, by the research project “Mathematics Education in Costa Rica”, designed by researchers at the Centro de Investigaciones Matemáticas y Meta-Matemáticas of the Universidad de Costa Rica.